Strategi pemasaran media sosial untuk UMKM kuliner: Implementasi business plan pentol gledek - MA’RIFATUNNISA, MA’RIFATUNNISA MA’RIFATUNNISA; ROMADLONI, PUTRI ANGGUN (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of social media in implementing the Pentol Gledek business plan for culinary micro, small, and medium enterprises (UMKM). The article aims to analyze effective social media marketing strategies for these enterprises. Digitalization has changed the marketing context; social media has become the main platform for increasing the visibility and sales of culinary products. This article uses a qualitative method to analyze the implementation of digital marketing strategies in culinary UMKM. Data and observations were obtained through the author’s experience selling Pentol Gledek for two weeks, during which two sales were made via a pre-order system. The product was consistently promoted and sold through platforms such as WhatsApp and Instagram every day. Additionally, data was obtained through the analysis of social media content. The results show that effective social media marketing strategies include choosing the right platform, creating interesting and consistent content with a focus on food photography, and building engagement by actively interacting with consumers and responding quickly to their feedback. Implementing a business plan integrated with social media increases brand awareness, customer engagement, and sales for culinary UMKM. It also expands market reach from local to regional environments and increases brand recognition. Successful product marketing on social media requires consistent content and adaptation to social media trends. This article provides culinary UMKM with a practical digital marketing framework and offers academics insights into digital marketing and the development of effective business plans in today’s digital era.